Weighted Maps: Treemap visualization of geolocated quantitative data - Mohammad Ghoniem; Maël Cornil; Bertjan Broeksema; Mickaël Stefas; Benoît Otjacques (VDA'15: Proceedings of the Conference on Visualization and Data Analysis, 2015)
A wealth of census data relative to hierarchical administrative subdivisions are now available. It is therefore desirable for hierarchical data visualization techniques, to offer a spatially consistent representation of such data. This paper focuses on a widely used technique for hierarchical data, namely treemaps, with a particular emphasis on a specific family of treemaps, designed to take into account spatial constraints in the layout, called Spatially Dependent Treemap (SDT). The contributions of this paper are threefold. First, we present the ``Weighted Maps'', a novel SDT layout algorithm and discuss the algorithmic differences with the other state-of-the-art SDT algorithms. Second, we present the quantitative results and analyses of a number of metrics that were used to assess the quality of the resulting layouts. The analyses are illustrated with figures generated from various datasets. Third, we show that the Weighted Maps algorithm offers a significant advantage for the layout of large flat cartograms and multilevel hierarchies having a large branching factor.